Pengaruh Serangan Keamanan Pada Vanet Terhadap Performansi Jaringan - Alfon Sera; Linna Oktaviana Sari (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2019)
Information and communication technology developing are very rapidly, because human needs keep growing. Human safety in driving is one of the important factors in technological development. VANET is communication between vehicles, so that it can be used as a smart traffic information system. The VANET network is an ad-hoc network that does not have a fixed infrastructure and the rapidly changing network topology VANET is vulnerable to various attacks. Analysis of AODV routing protocol using 150 nodes with no attack and with blackhole attack scenario. This research uses Network Simulator 2 and SUMO software to make a model of node mobility. The results show that the network simulated without attack has 99.56% PDR value the PDR value with blackhole attack is 0%. In conclusion, VANET network performance is otherwise influential towards blackhole attack because, the difference value lotwes no attack PDR value & blackhole attack PDR value is so significant.Keywords : VANET, AODV, Blackhole, PDR.